DEVELOPMENT OF A MODIFIED NUMERICAL SOLUTION FOR BOTTOMHOLE PRESSURE RESPONSE DURING WATER INJECTION / FALLOFF TESTING - MOHAMED ALTHAF, MOHAMED SHAFEER (2020)
The development of a mathematical solution for injection/falloff problem of an oil-water system for transient data analysis is complicated due to the presence of two mobile phases that create a moving discontinuity. The models that have been developed in the past have neglected one or more key reservoir configurations such as the saturation gradient behind the front, temperature effects, wellbore storage, skin and the outer boundary conditions that make the models limited. The intents of this study are to (1) present a generalized modified numerical solution method to precisely simulate the pressure transient behaviour for injection and falloff tests following cold water injection for a fully-penetrating vertical well in a warm and bounded oil reservoir in the presence of skin and wellbore storage and (2) perform sensitivity analysis to study the factors that influence the pressure transient behaviour using the formulated model.